Studi Fenomenologi Pengembangan Implementasi Layanan Blud Berbasis Teori Sistematis Kesehatan Donabedian di Puskesmas Sedan Kabupaten Rembang - Aka Pravita Septiana; Tri Ismu Pujiyanto; Witri Hastuti (Universitas Pahlawan Tuanku Tambusai, 2026)
Community Health Centers (Puskesmas) as the main pillar of primary health care in Indonesia face limitations in budget, human resources, and bureaucratic processes. The implementation of the Regional Public Service Agency (Badan Layanan Umum Daerah/BLUD) financial management system has become a strategic approach to improving managerial flexibility and service quality. This study aimed to develop the implementation of BLUD at Puskesmas Sedan, Rembang Regency, based on Donabedian’s health system framework, which encompasses structural, process, and outcome dimensions. This study employed a phenomenological qualitative approach involving four key participants: the Head of the Community Health Center, the Technical Implementation Officer (PPTK), the BLUD Treasurer, and health personnel directly involved in BLUD management. Data were collected through in-depth interviews, participatory observation, and document review, and analyzed using Colaizzi’s thematic analysis method. The findings identified four main themes: adjustment of the BLUD system, limitations in human resources, improvements in efficiency and service quality, and the role of local government support. The implementation of BLUD was shown to enhance managerial flexibility and service quality, although challenges related to human resource capacity and reporting requirements remain.